2018
DOI: 10.1021/acsnano.8b02053
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Extracellular Vesicles by Fusion with Liposomes for the Design of Personalized Biogenic Drug Delivery Systems

Abstract: Extracellular vesicles (EVs) are recognized as nature's own carriers to transport macromolecules throughout the body. Hijacking this endogenous communication system represents an attractive strategy for advanced drug delivery. However, efficient and reproducible loading of EVs with therapeutic or imaging agents still represents a bottleneck for their use as a drug delivery system. Here, we developed a method for modifying cell-derived EVs through their fusion with liposomes containing both membrane and soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
266
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(269 citation statements)
references
References 71 publications
(107 reference statements)
3
266
0
Order By: Relevance
“…[ 60–63 ] However, current studies involving EVs delivery systems mainly focus on the synthetic hydrogels or matrix. [ 64–66 ] Notably, polymers that are not water‐soluble may not be suitable to encapsulate EVs, and the residual unreacted cross‐linkers for hydrogel making increase the potential toxicity. [ 67 ] In addition, the processing of these polymers normally involves a strong organic solvent, which may degrade the structural integrity and content of the exosomes when mixed.…”
Section: Resultsmentioning
confidence: 99%
“…[ 60–63 ] However, current studies involving EVs delivery systems mainly focus on the synthetic hydrogels or matrix. [ 64–66 ] Notably, polymers that are not water‐soluble may not be suitable to encapsulate EVs, and the residual unreacted cross‐linkers for hydrogel making increase the potential toxicity. [ 67 ] In addition, the processing of these polymers normally involves a strong organic solvent, which may degrade the structural integrity and content of the exosomes when mixed.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, improving the EVs loading and delivering efficiency is one aspect that has been reconsidered, due to a discrepancy in the published protocol and data reproducibility [66]. Piffoux et al published a method for loading EVs using liposomes and showed impressive results [67]. However, the efficacy of this protocol has not been confirmed.…”
Section: Evs As Therapymentioning
confidence: 99%
“…A promising compromise between EVs and liposomes was made by Piffoux et al, in 2018. [267] They fused EVs with liposomes to allow better cargo loading while preserving the natural vesicular membrane moieties, stability, and thus the EV identity. The fusion protocol was optimized by fusing 1,2-dioleoyl-snglycero-3-phospho-Lserine-N-(7-nitro-2−1,3-benzoxadiazol-4-yl) (NBD-PS) and 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine-N-(lissamine rhodamine B sulfonyl) (Rho-PE) lipids within the membrane of nonfluorescent EVs, resulting in increased NBD fluorescence, due to the lack of fluorescence resonance energy transfer (FRET).…”
Section: Hybrid Vesiclesmentioning
confidence: 99%